Vanguard - Aguirre, Ann (Aguirre, Ann. Razorland trilogy, 2017)
Tegan signs on as a ship's doctor, hoping for an epic adventure, but soon finds romance with Szarok, the Uroch vanguard, in a relationship that is both alien and forbidden.